PENGARUH KEPEMILIKAN ASING, SOLVABILITAS, LIKUIDITAS, DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di BEI Tahun 2013-2016) - Arfansyah, Arfansyah; Savitri, Enni; putra, Adithya Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine: 1) the effect of foreign ownership on corporate social responsibility disclosure, 2) the influence of solvability on corporate social responsibility disclosure, 3) the effect of liquidity on corporate social responsibility disclosure, 4) the influence of the size of the board of commissioners towards corporate social responsibility. The population used in this study is a mining sector company listed on the Indonesia Stock Exchange in 2013-2016. Samples were determined by using purposive sampling method and obtained sample of 15 companies with a total of 41 observations. The type of data used in this study is secondary data. Data analysis was done by multiple regression analysis using SPSS program. The results of the research indicate that: 1) foreign ownership influences corporate social responsibility disclosure, 2) solvability influences corporate social responsibility disclosure, 3) liquidity influences corporate social responsibility disclosure, 4) the size of the board of commissioners has no effect on corporate social responsibility disclosure.Keywords : Foreign Ownership, Solvency, Liquidity, Size of Board of Commissioners, Disclosure of Corporate Social Responsibility